2018
DOI: 10.1016/j.yebeh.2018.01.037
|View full text |Cite
|
Sign up to set email alerts
|

Italian Wikipedia and epilepsy: An infodemiological study of online information-seeking behavior

Abstract: Wikipedia is the most commonly accessed source of health information by both healthcare professionals and the lay public worldwide. We aimed to evaluate information-seeking behavior of Internet users searching the Italian Wikipedia for articles related to epilepsy and its treatment. Using Pageviews Analysis, we assessed the total and mean monthly views of articles from the Italian Wikipedia devoted to epilepsy, epileptic syndromes, seizure type, and antiepileptic drugs (AEDs) from January 1, 2015 to October 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Several other studies showed that interest in MS on Wikipedia was higher than the interest in other neurological diseases [8,9].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Several other studies showed that interest in MS on Wikipedia was higher than the interest in other neurological diseases [8,9].…”
Section: Discussionmentioning
confidence: 93%
“…Some studies have shown that online interest in borreliosis and in West Nile virus disease correlates with their prevalence [7]. Most studies of neurological diseases did not show a correlation of web visitors' interest with the disease prevalence [3,8]. A study investigating Wikipedia visits related to the most common neurological diseases (MS, AD, stroke, epilepsy) did not find any relation between the incidence or prevalence of neurological disorders and the search volume for the related Wikipedia articles.…”
Section: Discussionmentioning
confidence: 98%
“…Utilising the infodemiology approach to study temporal patterns and variations, Jonas Tana, Emil Eirola and Kristina Eriksson-Backa report on rhythmicity of health information behaviour. Although there are papers reporting the use of infodemiology in health-related information behaviour from medical perspectives, e.g., Brigo et al (2018) reporting on online information seeking related to the Italian Wikipedia and epilepsy, Hill et al (2011) on internet searches for H1N1 influenza, Zhang et al (2013) on the use of twitter to monitor physical activity and Blomberg et al (2019) on using a Facebook forum to cope with narcolepsy after pandemrix vaccination, there is very limited mention of infodemiology in the Information Science literature and hardly any in information behaviour research. Although a focus on the temporal is also not new in information behaviour research (Amitay et al, 2004;Combi and Shahar, 1997;Kimia and Ahmadi, 2018;Rahmi et al, 2019;Savolainen, 2018), it is certainly a novel addition when combined with infodemiology, and is an approach that could trigger interesting research.…”
Section: Infodemiology Approach To Study Temporal Patterns and Variationsmentioning
confidence: 99%